Umbilical cord clamping and preterm infants: a randomised trial. Issue 6871 (16th January 1993) - Kinmond, S; Aitchison, T C; Holland, B M; Jones, J G; Turner, T L; Wardrop, C A
Abstract : OBJECTIVE--To investigate the clinical effects of regulating umbilical cord clamping in preterm infants. DESIGN--A prospective randomised study. SETTING--The Queen Mother's Hospital, Glasgow. SUBJECTS--36 vaginally delivered infants over 27 and under 33 weeks' gestation. INTERVENTION--Holding the infant 20 cm below the introitus for 30 seconds before clamping the umbilical cord ("regulated" group, 17 patients), or conventional management ("random" group, 19 patients). MAIN OUTCOME MEASURES--Initial packed cell volume, peak serum bilirubin concentrations, red cell transfusion requirements, and respiratory impairment (assessed by ventilatory requirements, arterial-alveolar oxygen tension ratio over the first day in ventilated infants, and duration of dependence on supplemental oxygen). RESULTS--There were statistically significant differences between the two groups in mean initial packed cell volume (regulated group 0.564, random group 0.509) and median red cell transfusion requirements (regulated group zero, random group 23 ml/kg). 13 infants from each group underwent mechanical ventilation and showed significant differences in mean minimum arterial-alveolar oxygen tension ratio on the first day (regulated group 0.42, random group 0.22) and in median duration of dependence on supplemental oxygen (regulated group three days, random group 10 days). Differences in final outcome measures such as duration of supplemental oxygen dependence and red cell transfusion requirements were mediated primarily through arterial-alveolar oxygen tension ratio and also packed cell volume. CONCLUSIONS--This intervention at preterm deliveries produces clinical and economic benefits.